2013
DOI: 10.7813/jes.2013/4-2/3
|View full text |Cite
|
Sign up to set email alerts
|

Employment of active learning in classroom management and it’s effect on students’ academic success

Abstract: The employment of active learning in classroom management, which centers individual and values the selfcreation in educational process, and the effect of this method on students have been analysed in this study. As the method of the study, action research procedure of qualitative research method is employed.The acquired-data of the study have been analysed by SPSS (Statistical Package for Social Sciences) for Windows 17.0 programme. The descriptive norms ( numbers, percentages) are used during the process of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Students who have been equipped with theories and basic principles will have a better understanding of the material goals so students will be easier to follow the lessons well and actively involved in conveying the material that has been acquired during the process Learning. Active learning will lead to a longer-lasting understanding of concepts (Odabaşi & Kolburan, 2013).…”
Section: Results Of Quantitative Analysis On Inductive and Deductive Amentioning
confidence: 99%
“…Students who have been equipped with theories and basic principles will have a better understanding of the material goals so students will be easier to follow the lessons well and actively involved in conveying the material that has been acquired during the process Learning. Active learning will lead to a longer-lasting understanding of concepts (Odabaşi & Kolburan, 2013).…”
Section: Results Of Quantitative Analysis On Inductive and Deductive Amentioning
confidence: 99%
“…The impacts of active learning methods in classroom management and students' academic success was studied by Odabasi and Kolburan who found that active learning helped them to remember the concepts permanently and this method is vital for their academic success. 40 Sometimes uses of chart, models, technology etc enhances students' academic performance. Pop-Pacurar and Tirla introduced models in biology classes as strategies of active learning and observed that students' average final score has increased by 2.03 points from the initial test whereas it was only 0.93 points who did not use models.…”
Section: Review Of Literaturementioning
confidence: 99%